EVALUATION OF TOCOLYTIC ACTIVITY OF AQUEOUS SEED EXTRACT OF SYZYGIUM CUMINI ON OXYTOCIN INDUCED PRETERM LABOR - M, RAMASAMY; SEBASTIAN, ANU; GEORGE, ASHLY MERIN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present investigation was aimed to determine the tocolytic activity of the aqueous seed extract of S. cumini (AESC) in animal models. Methods: The in vitro antioxidant activity of AESC was evaluated by (1, 1-diphenyl-2- picrylhydrazyl (α,α-diphenyl-β-picrylhydrazyl) and (2,2’-azino-bis(3- ethylbenzothiazoline-6-sulfonic acid) ABTS radical scavenging assay which showed the hydrogen donating and free radical scavenging activity of extract that aids in the prevention of preterm labor. In vivo tocolytic activity of AESC was evaluated. The level of in vivo antioxidant parameters such as catalase, superoxide dismutase (SOD) and glutathione was restored in the treated group compared to the control group. The AESC was subjected to pharmacological testing in vitro on a piece of isolated rat uterus previously pretreated with estradiol valerate, concentrations used were 80 mg/ml and 160 mg/ml. Results: The study showed the promising radical scavenging activity of the extract due to hydrogen-donating ability of the formulation. In the current study, a significant increase in the rate of preterm delivery (PTD) of the control animals was observed when compared with the normal group. The AESC treated group has showed a significant reduction in the rate of PTD which was comparable with the standard treated group as well as the normal group. The study reveals that the extracts have been able to increase the endogenous antioxidant enzyme activities while reducing the lipid peroxidation. The concentrations (80 mg/ml) and (160 mg/ml) produce 50.9% and 70.9 % inhibition, respectively. Conclusion: The results indicate the presence of active principles in the AESC which may be responsible for the tocolytic activity.